Insights into the metabolic basis of the halotolerant Pseudomonas aeruginosa strain LVD-10 during toluene biodegradation - Drakou, Efi Maria; Koutinas, Michalis; Pantelides, Iakovos; Tsolakidou, Maria Dimitra; Vyrides, Ioannis (My University, 2015)
In this work a Pseudomonas aeruginosa strain (LVD-10) has been isolated from activated sludge, based on its capability to biodegrade toluene under extreme conditions. In 0, 20 and 40gL-1 NaCl the percentage of toluene removal reached 86%, 98% and 89% within 24h, respectively. Interestingly, the removal of toluene occurred significantly faster compared to biomass growth, while the strain achieved 79.1% and 91.7% of 1mLL-1 diesel removal after 7 days at 0 and 30gL-1 NaCl, respectively. The pathways used by LVD-10 were determined through PCR amplification of genes that encode key enzymes involved in aromatics degradation and genes of the Quorum Sensing (QS) system. The genes XylE1, 1,2-CTD, 2,3-CTD, rhlR1 and rhlR2 were detected in LVD-10 whereas tbmD, TodC1 and Rmo were not found. The transcription level of genes measured by Q-PCR did not show any significant variation in gene expression of cells stimulated with salinity conditions of 30gL-1 NaCl. However, when NaCl was increased to 50gL-1 the genes were significantly down-regulated 48h after toluene induction, while the expression of genes was restored to normal levels at 120h. Furthermore, the expression of genes RhlI and RhlR2, which have been proposed to be involved in the Quorum Sensing (QS) system of P. aeruginosa, indicates that the strain has great ability to tolerate toxic environments as well as to perform efficient degradation of aromatic hydrocarbons.
Keywords: Diesel biodegradation; Pseudomonas aeruginosa; Salinity; Toluene; Toluene catabolic genes